Executive functions and psychosocial impairment in children following arterial ischemic stroke. Issue 2 (17th February 2023) - Rivella, Carlotta; Zanetti, Alice; Bertamino, Marta; Severino, Mariasavina; Primavera, Ludovica; Signa, Sara; Moretti, Paolo; Viterbori, Paola
ABSTRACT: This study examined the executive function (EF) of children with a history of arterial ischemic stroke (AIS) and preserved intellectual abilities, with reference to age at stroke onset, lesion characteristics, language, and motor functioning. In addition, the associations between EF and emotional and behavioral functioning were investigated. A battery of standardized neuropsychological tests was administered to children with previous AIS aged 7–12 in order to assess EF, including inhibition, working memory, cognitive flexibility, and attention. Parents rated questionnaires regarding real-life emotional and behavioral functioning. Finally, clinical and neuroradiological data were also gathered. Thirty patients were enrolled. Eight children fall in the lower end of the normative range or below in more than half of the EF measures, with working memory, inhibition and cognitive flexibility equally impaired, and attention relatively better preserved. Larger lesion size and language deficits were significantly associated with higher EF impairment. Emotional and behavioral functioning was lower in children with weaker EF. Children with a history of AIS, even those with preserved intellectual functioning, have a high risk of showing poor EF, mostly regardless of clinical features or functional impairment. EF difficulties are in turn associated with emotional and behavioral problems. Therefore, a standardized evaluation of EF in this population is mandatory as part of the follow-up, in order to ensure an early intervention and prevent related difficulties.